Evaluasi Efek Relationship Marketing Pada Pelayanan Skin Care di Rumah Sakit PKU Muhammadiyah Yogyakarta - Nasiatul Aisyah Salim; susilowati . (Jurnal Kesehatan Komunitas, 2013)
Skin care is a service which is taken into account by PKU Muhammadiyah Yogyakarta hospital as a way to cope with the competition among the hospitals. PKU Muhammadiyah Yogyakarta skin care was established in July, 2010. In a year, visit amount had fluctuated. One fluctuated impact is negative evaluation of market because hospital can not control skin care service. marketing evaluation a principles on relationship marketing. Handled fluctuated way of marketing evaluation principled on relationship marketing. To evaluate of relationship marketing on skin care service in PKU Muhammadiyah Yogyakarta Hospital. This research used a mixed method with design sequential explanatory. The subject quantitative is 112 respondents and subject qualitative is 7 respondents selected from subject quantitative. The data was taken from questionnaires and in-depth interviews. The data analysis is double linear regression. Communication have association on trust, commitment and relationship satisfaction.Relationship duration have association on commitment and relationship satisfaction. Interaction frequency have no association on trust. Commitment and relationship satisfaction have association on word of mouth. Factors affecting no customer commitment is customer must wait whereas did appoitment, beautician can not answer the question of customers, no drugs in pharmacy and no resulting skin care in PKU Muhammadiyah Yogyakarta Hospital. Commitment and relationship satisfaction have association on word of mouth. Communication and relationship duration can increase of commitment and relationship satisfaction